Conflicting interests over natural resource use: the case of interactions among livestock keepers, farmers, and wildlife at Kilombero Valley, Tanzania - Mariki, Sayuni B.; Binego, Liliane (Frontiers in Sustainable Resource Management, 2025)
Conflicts over natural resources use among farmers, livestock keepers, and wildlife are escalating in the Kilombero Valley, Tanzania, posing significant threats to livelihoods, security, and sustainable development. This study investigated the types, drivers and impacts of these conflicts using a mix-methods approach, including questionnaire survey, key informant interviews, and focused group discussions. Descriptive statistics and content analysis revealed 16 distinct conflict types, with the most prevalent being crop raiding by livestock before harvest (farmers-pastoralist conflict) and disputes over farm boundaries (farmer-farmer conflict). Key drivers of conflicts varied between groups but commonly included an increasing number of livestock, inadequate supervision of herders, and seasonal flooding of grazing lands. The primary consequences identified were reduced crop yields, social tension, and emotional distress. To mitigate these conflicts, the study recommends enforcing adherence to village land use plans, promoting coexistence through community education, providing training in livestock management and good practice, and regulating livestock influx into the area.